Analysis of Contract for Umrah Financing Products at Kalsel Sharia Bank - Rahmatul Huda (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
Umrah financing products are available in sharia financial institutions including sharia banks. In fact, in the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) there is no specific fatwa that regulates Umrah financing. Based on article 26 of Law Number 21 of 2008 concerning Sharia Banking, it states that business activities and/or products and services of sharia banks must comply with sharia principles, namely referring to the DSN-MUI Fatwa. Based on this background, the author is interested in researching how the Umrah financing product is practiced in sharia banks with the contract approach and sharia conformity in the implementation of the Umrah financing product at the South Kalimantan Syariah Bank. The aim of this research is to determine the Umrah financing product at Bank Kalsel Syariah and to analyze the contract. This type of research is empirical legal research, which is qualitative in nature using descriptive methods. The results of the study indicate that Bank Kalsel Syariah's Umrah financing product is sharia financing for Umrah pilgrimage trips. The implementation of this product refers to the DSN MUI Fatwa Number: 44/DSN-MUI/VIII/2004 concerning Multiservice Financing. The Umrah financing product at Bank Kalsel Syariah uses an Ijarah contract, the implementation of which follows the provisions in the DSN MUI Fatwa Number: 09/DSN-MUI/IV/2000 concerning Ijarah Financing. With this product, Bank Kalsel Syariah can receive service compensation (ujrah) or fees, the amount of which has been agreed at the beginning and is expressed in nominal form.